Inscriptions urbaines, autorités publiques et contestations : le cas du rayado à Santiago du Chili - Jean-Baptiste Barra (Les Cahiers de Framespa)
Between censorship and promotion, the Chilean mural maintains complex relationships with the Santiago’s municipal public authority. If, today, a lot of practices benefit from the support and from the help of the capital, in the name of the conservation of the heritage and from the cultural dynamism, some are always object of an active repression. What about the rayado, traditional popular practice become today a generic word denoting all the unwanted inscriptions ? Isn’t the rayado a victim of its own communications strategies ? In confrontation with it’s recipients, these citizens’ scream are rejected by public authorities and by an important part of the Chilean society. The purpose is to highlight the paradoxes which characterize and lead the contemporary relation between these wall inscriptions and the public authority, by taking as example the Catedral Metropolitana and Puente Matta’s envents.